Internal Wind Driven Ocean Circulation Variability Delays the Time of Emergence of Externally Forced Sea Surface Temperature Trends - Sarah M. Larson; Kay McMonigal (Geophysical Research Letters)
Abstract In parts of the global ocean, large internal variability continues to mask the detection of externally forced sea surface temperature (SST) trends in observations and climate models. Such regions of large internal variability are typically where wind driven ocean dynamical processes contribute heavily to SST variability. Through analysis of two climate model ensembles, we find that internal wind driven ocean circulation variability delays the time of emergence of SST signals nearly everywhere, but the delay is longest (>10 years) in dynamically active regions like the tropical oceans. We also find that internal wind driven ocean circulation variability is the dominant contributor to changes in the amplitude of internal SST variability over the historical period. Results suggest that inter‐model differences in wind driven SST variability may be a key contributor to inter‐model differences in the time of emergence of externally forced SST signals in climate change scenarios.